Süt sığırlarında damızlık değerin tahmininde değişik yöntemlerin kullanımı - Kızılkaya, Kadir (Fen Bilimleri Enstitüsü, 1993)
As research material, 322 lactation milk yields recorded between 1975 and 1991 from 131 daughter cows of 13 sires of the black and white dairy herd in the. Ankara Sugar Factory Farm were evaluated. In this study, breeding values of sires and dams have been estimated with different methods (Herdmate Comparison, Contemporary Comparison, Best Linear Unbiased Predict ion (BLUP) Methods), as well as the real producing ability of dams. Also, the genetic trend of the herd was found for the years between 1981 and 1989. The correlations among breeding values estimated through different methods were found to be 0. 852-0. 993, 0. 756- 1. 000 for sires and dams respectively, and rank correlations among them, in the same order, were estimated 0.841-0.989, 0.744-0.999.IV Although the relations between methods (BLUPR1, BLUPR2) considered relationship and the other methods were low, correlations between breeding values and real producing ability of dams were calculated 0.772-0.992. The comparison of methods based on the correlation coefficients showed that the methods were not significantly different. But, it was suggested to prefer BLUPRi since this method used the »hole data and gave more detailed results. Key Words : Breeding value, Transmitting ability, Herdmate comparison, Contemporary comparison, Best linear unbiased prediction, Relationship matrix, Real producing ability, Genetic trend
Application of different methods in the estimation of breeding values in dairy cattle
Keywords: Damızlık değeri